Letter to the Editor: Significant mutation enrichment in inverted repeat sites of new SARS-CoV-2 strains - Bartas, Martin; Goswami, Pratik; Lexa, Matej; Červeň, Jiří; Volná, Adriana; Fojta, Miroslav; Brázda, Václav; Pečinka, Petr (Briefings in bioinformatics, 2021)
In a recently published paper, we have found that SARS-CoV-2 hot-spot mutations are significantly associated with inverted repeat loci and CG dinucleotides. However, fast-spreading strains with new mutations (so-called mink farm mutations, England mutations and Japan mutations) have been recently described. We used the new datasets to check the positioning of mutation sites in genomes of the new SARS-CoV-2 strains. Using an open-access Palindrome analyzer tool, we found mutations in these new strains to be significantly enriched in inverted repeat loci.
Keywords: mutace; genom virový; lidé; Genome, Viral; inverted repeats; SARS-CoV-2; mutations; Mutation; COVID-19; Humans